A Mini Review on Yolk-Shell Structured Nanocatalysts - Sun, Xiaohuan; Han, Jie; Guo, Rong (Frontiers in Chemistry, 2020)
Yolk-shell structured nanomaterials, possessing hollow shell and interior core, are emerging as unique nanomaterials with the application ranging from material science, biology and chemistry. In particular, with interesting scaffold, yolk-shell structure shows great promise as nanocatalyst. Basically, the hollow shell constructed for the yolk-shell offers confined space for the active yolk, keeping them from aggregation and deactivation. In addition, many strategies can be adopted to further endow the yolk-shell based nanocatalyst with superior catalytic performance. In this minireview, the synthetic methods for the preparation of various yolk-shell nanomaterials is provided first. Then, the strategies to improve the catalytic performance of yolk-shell catalyst with the engineering of shell, yolk, void and related synergistic effect are mainly exemplified. In the end, the challenges and prospects for yolk-shell nanocatalysts are discussed.